1998
DOI: 10.1089/clm.1998.16.153
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulpal Temperature during Preparation with the Er:YAG Laser Compared to the Conventional Burr: An in Vitro Study

Abstract: The reduction in pain with clinical use of the Er:YAG laser for class V cavities has already been mentioned in publications and could, in addition to the nontactile preparation, be due to the lesser increase in intrapulpal temperature during the laser preparation in comparison to the conventional burr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 4 publications
1
59
0
9
Order By: Relevance
“…Some Er:YAG laser beams could penetrate to deeper areas than the ablated area and damage the nerve fi bres and terminals, which might be a mecha nism of pain reduction in cavity ablation with the Er:YAG laser. 1 A number of authors 10,13,16,[18][19][20][21][22][23] stud ied the behaviour of different lasers to determine the amount of temperature increase during cavity preparation on dental structure. Keller et al (2003) 19 verified a mean temperature rise of 1.68ºC in the pulpal chamber using CO 2 and morphologically unaltered dentine surfaces, demonstrat ing the safe and tissue preserving char acter of the laser.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some Er:YAG laser beams could penetrate to deeper areas than the ablated area and damage the nerve fi bres and terminals, which might be a mecha nism of pain reduction in cavity ablation with the Er:YAG laser. 1 A number of authors 10,13,16,[18][19][20][21][22][23] stud ied the behaviour of different lasers to determine the amount of temperature increase during cavity preparation on dental structure. Keller et al (2003) 19 verified a mean temperature rise of 1.68ºC in the pulpal chamber using CO 2 and morphologically unaltered dentine surfaces, demonstrat ing the safe and tissue preserving char acter of the laser.…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that the elevation meas ured in the pulp chamber during lasing with various energies and pulse rates was low and did not exceed the critical value of 5.5ºC. 5 There are few reports 14,20,24 compar ing the intrapulpal temperature rise during tooth preparation with Er: YAG laser and conventional burs with confl icting fi ndings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,12 Over this period, a number of problems have emerged with regard to the efficiency with which the laser cuts enamel and dentin. 17 Most attempts to increase the output energy of the laser have been motivated by the need for improved ablation efficiency, [18][19][20][21] but little is known about the effects of variable irradiation conditions on ablation efficiency. Therefore, we assessed the effects of output power, output energy, and pulse repetition rate on the amount and depth of ablation of dentin to identify the clinically optimal ablation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased pulpal temperature, during erbium laser cavity preparation, has been shown to be equivalent to a high-speed dental turbine with water spray [11]. In fact, some research has shown a reduction in pulpal temperature with the Er:YAG preparation when compared to conventional burrs [12]. The Er,Cr:YSGG laser is a free-running pulsed (FRP) laser system which delivers energy in the mid-infrared spectrum, through a fiber-optic trunk fiber with contra-angle handpiece (HP) that resembles a high-speed drill.…”
Section: Introductionmentioning
confidence: 99%